2007
DOI: 10.1038/sj.tpj.6500476
|View full text |Cite
|
Sign up to set email alerts
|

The influence of fluorouracil outcome parameters on tolerance and efficacy in patients with advanced colorectal cancer

Abstract: The purpose of this study was to determine simple genetic factors helpful to tailor 5-FU administration and determine strategy in first-line chemotherapy of advanced colorectal cancer. In 76 patients initially treated by 5-FU, thymidylate synthase, dihydropyrimidine dehydrogenase and methylene tetrahydrofolate reductase germinal polymorphisms, dihydrouracil/uracil plasma ratio and 5-FU plasma clearance were investigated and correlated for tolerance (10.5% grade 3 and 4 toxicity) and efficacy (32.9% objective r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
2
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(69 citation statements)
references
References 30 publications
2
63
2
2
Order By: Relevance
“…Capitain and colleagues analyzed the potential effect of genetic factors on 5-FU metabolism and the correlation with tolerance and efficacy in 76 patients with mCRC receiving PK-monitored infusional 5-FU chemotherapy [78]. In this patient cohort, 3.9% (3 patients) were heterozygous for DPD variants.…”
Section: Dihydropyrimidine Dehydrogenase (Dpd)mentioning
confidence: 99%
“…Capitain and colleagues analyzed the potential effect of genetic factors on 5-FU metabolism and the correlation with tolerance and efficacy in 76 patients with mCRC receiving PK-monitored infusional 5-FU chemotherapy [78]. In this patient cohort, 3.9% (3 patients) were heterozygous for DPD variants.…”
Section: Dihydropyrimidine Dehydrogenase (Dpd)mentioning
confidence: 99%
“…Previous studies have shown contradicting results with regard to the role of MTHFR in toxicity in relation to 5-FU chemotherapy (6,13,17,(33)(34)(35). The contradictory results may reflect that the MTHFR 677C>T and MTHFR 1298A>C SNPs were not combined according to phenotypic effects, differences in treatment regimens, and inadequate statistical analyses.…”
Section: Discussionmentioning
confidence: 94%
“…These results are in accordance with previously published results indicating an effect on toxicity of decreased MTHFR activity. 29,61 A curious finding, also noted by Gene variants in DPYD, MTHFR and TYMS predict 5-FU-related toxicity Sharma et al,62 was that the MTHFR 677 C/T heterozygous genotype significantly predicted toxicity (RR 1.38; P = 0.03).…”
Section: Discussionmentioning
confidence: 96%